Dada: Art And Anti Art (Thames & Hudson, 1964)
(3z(BWhere and how Dada began is almost as difficult to determine as Homer$1 (Bs birthplace,(3y (Bwrites Hans Richter, the artist and filmmaker closely associated with this radical movement from its earliest days. Here he records and traces Dada$1 (Bs history, from its inception in wartime Zurich to its collapse in Paris in the 1920s, when many of its members joined the Surrealist movement, to the present day when its spirit reemerged in the 1960s in movements such as Pop Art. This absorbing eyewitness narrative is enlivened by extensive use of Dada documents, illustrations, and texts by fellow Dadaists.s
English
Keywords: Dadaism; N5300-7418 Visual Arts- History